Potential effects of pomegranate on lipid peroxidation and pro-inflammatory changes in daunorubicin-induced cardiotoxicity in rats - Hayder M Al-Kuraishy; Ali I Al-Gareeb (International Journal of Preventive Medicine, 2016)
Background: Daunorubicin-induced acute cardiotoxicity caused by oxidative stress and free radical formation. Pomegranate possessed a significant in vitro free radical scavenging activity. Therefore, the aim of this study was estimations of the role of pomegranate effects in daunorubicin-induced cardiotoxicity. Methods: A total of 21 Sprague male rats were allocated into three groups, seven animals in each group. Group A: Control group received distilled water. Group B: Treated group with daunorubicin 20 mg/kg via intraperitoneal injection daily for the 12 th day for total cumulative dose of 240 mg/kg. Group C: Pretreatment group with pomegranate 25 mg/kg for 6 days orally, then daunorubicin 20 mg/kg administrated concomitantly for the next 6 days with a cumulative dose of 120 mg/kg. Cardiac troponin I [cTn I] pg/ml), malondialdehyde (MDA) (ng/ml), interleukin 17 (IL-17 pg/ml), and cardiac lactate dehydrogenase (LDH) (pm/ml), all these biomarkers were used to measure the severity of cardiotoxicity. Results: Daunorubicin at a dose of 20 mg/kg lead to pronounced cardiac damage that reflected on through elevations of serum cTn and serum LDH levels significantly P < 0.01, it induced lipid peroxidation during cardiotoxicity that reflected through an elevation in the serum MDA significantly P < 0.01, moreover, daunorubicin induces pro-inflammatory changes in cardiotoxicity; it raises the IL-17 serum level significantly P < 0.01 as compared with control. Pomegranate pretreatment demonstrated a significant cardioprotection from daunorubicin-induced cardiotoxicity; it attenuated the cardiac damage through reduction of cTn, LDH, MDA, and serum IL-17 level significantly P < 0.01 as compared with daunorubicin-treated group. Conclusions: Pomegranate demonstrated significant cardioprotection in daunorubicin-induced cardiotoxicity through reduction of oxidative stress, lipid peroxidation, pro-inflammatory, and cardiac injury biomarkers.